A novel predictor of persistent ocular hypotony after pars plana vitrectomy for rhegmatogenous retinal detachment: The initial intraocular pressure difference between the eye with RRD and the fellow eye - ÖZGÜR, EMRAH GÖKAY (My University, 2025)
Purpose: To evaluate the predictive value of initial intraocular pressure difference of the detached and fellow eyes of patients with complex rhegmatogenous retinal detachment on postoperative persistent ocular hypotony. Methods: This retrospective observational study included 538 eyes of 538 unilateral complex rhegmatogenous retinal detachment patients with a proliferative vitreoretinopathy grade of C-1 or higher, treated with silicone oil endotamponade following pars plana vitrectomy. The patients were divided into Group A (patients having silicone oil removal without ocular hypotony; n=504) and Group B (patients with persistent ocular hypotony following silicone oil removal [n=8, 23.5%] and with retained silicone oil [n=26, 76.5%] due to the risk of persistent ocular hypotony; total n=34). Ocular hypotony was defined as an intraocular pressure of <6 mmHg on two or more occasions. Patients’ demographics, including age, sex, and follow-up time, and ocular characteristics, including ocular surgical and trauma history, initial and final best-corrected visual acuity, intraocular pressure and initial intraocular pressure difference of the detached and fellow eyes, and anatomical success rates and postoperative complications, were retrospectively collected from the electronic patient files. Results: The initial intraocular pressure was significantly lower in the detached eyes of Group B than in Group A (8.3 ± 3.5 vs. 12.9 ± 3.3, p<0.001). Also, the initial intraocular pressure difference was significantly higher in Group B than in Group A (8.9 ± 3.2 vs. 2.2 ± 2.7mmHg, p<0.001). The receiver operating characteristic curve analysis showed that the cutoff value of the initial intraocular pressure difference was 7.5mmHg for the risk of persistent ocular hypotony. The most influential factors on postoperative persistent ocular hypotony in the binary logistic regression analysis were the initial intraocular pressure difference and the need for a retinectomy. Conclusion: In eyes with complex rhegmatogenous retinal detachment treated with pars plana vitrectomy and silicone oil tamponade, the initial intraocular pressure difference could be of value in predicting postoperative persistent ocular hypotony and could guide surgeons on the decision of silicone oil removal.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Eye Diseases and Surgery; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Göz Hastalıkları; Clinical Medicine (Med); Clinical Medicine; Ophthalmology; Oftalmoloji; Hypotony; Intraocular pressure; Ocular hypotension; Pars plana vitrectomy; Retinal detachment; Silicone oils; Visual acuity